The first rule [compact disc, unabridged] : a Joe Pike novel - Crais, Robert (Brilliance Audio, 2009)
The organized criminal gangs of the former Soviet Union are bound by what they call the thieves' code. The first rule is this: A thief must forsake his mother, father, brothers, and sisters. He must have no family, no wife, and no children. We are his family. If any of the rules are broken, it is punishable by death. Frank Meyer had the American dream, until the day a professional crew invaded his home and murdered everyone inside.